3x+6=-2x+41

Simple and best practice solution for 3x+6=-2x+41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=-2x+41 equation:


Simplifying
3x + 6 = -2x + 41

Reorder the terms:
6 + 3x = -2x + 41

Reorder the terms:
6 + 3x = 41 + -2x

Solving
6 + 3x = 41 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
6 + 3x + 2x = 41 + -2x + 2x

Combine like terms: 3x + 2x = 5x
6 + 5x = 41 + -2x + 2x

Combine like terms: -2x + 2x = 0
6 + 5x = 41 + 0
6 + 5x = 41

Add '-6' to each side of the equation.
6 + -6 + 5x = 41 + -6

Combine like terms: 6 + -6 = 0
0 + 5x = 41 + -6
5x = 41 + -6

Combine like terms: 41 + -6 = 35
5x = 35

Divide each side by '5'.
x = 7

Simplifying
x = 7

See similar equations:

| 3r+18/12=4r-24/4 | | 9.99+1.25*5= | | 9=-3/5x | | 9.99+1.25*4= | | -7/4=p/28 | | 7/2+12=6+5/2 | | 7/2+12=6+5/2 | | 9.99+1.25*3= | | 31=x+x+(x-1) | | X^3+x^2+9x+9=0 | | 9.99+1.25*2= | | 7x^2-40x-12x=0 | | a-(-6)=12 | | -12*(-55)*0= | | 8x+7=90 | | 5-x=(1/2x)+4 | | 4z+3z-6-7z=6 | | 7x=2x+1 | | -31+(-28)-(-14)-16= | | 8f-4=6f+26 | | 3y/x | | 3a+4b=(1-2c)/d | | (x/3)-4=5 | | 1/5x=10-5 | | 5(3+x)+1=71 | | 175.000+550.00-1.00x=220.650 | | -5+6x+4x^2+x^3=0 | | 3z+6=17 | | 0.5x+11=17 | | 9(x-5)=x+22(1/2) | | k/5+5=7 | | (-3/5)x=15 |

Equations solver categories